Digital Identity: Definition, Functions and Comparative Analysis of Ukrainian and European Union Legislation - Afonina, Olha (Teisė, 2025)
The world community’s shift from an industrial society to an information society has significantly affected all types of citizens’ political activities. More and more forms of political activity are being carried out while employing information and communication technologies. Due to their importance in developing e-democracy and ensuring citizens’ political rights and freedoms, digital forms of political activity are receiving constitutional and legislative foundations. As a part of e-democracy, digital identity is integral to constitutional mechanisms for the implementation of political rights. This research represents the different approaches to the definition of ‘digital identity’ as part of e-democracy and contains a comparison between Ukrainian and European Union legislation in this area. Although legal interest in this issue has been growing, it must be considered that e-democracy systems also incur requirements from the technological, sociological, and political sectors. By considering them, this article reveals perspectives on the Ukrainian legislation development in the field of digital identity as part of e-democracy. It concludes that Ukraine has the relevant legal acts defining the above-mentioned issues, but some issues are required to be harmonized with the European Union legislation.